IMPROVING THE QUALITY OF IPA LEARNING THROUGH EXAMPLE NON-EXAMPLE MODEL BY USING AUDIO-VISUAL MEDIA - Rizky Ardhi Wicaksono; Putri Yanuarita Sutikno (Jurnal Pendidikan dan Pembelajaran IPA Indonesia, 2019)
The purpose of this study was to improve the quality of IPA (Natural Sciences)  through Example Non-example model by using audio-visual media for fourth graders. This study used classroom action research method which consisted of three cycles with four stages, namely: planning, implementing, observation, and reflection. The collecting data used observation, interview, test, documentation, and field notes. The data were analyzed qualitatively and quantitatively. The result showed that the teacher’s skill in the cycle I gained score 51 (good), 57 in the cycle II (good), and 68 in the cycle III (very good).  The average score of students’ activity in the cycle I was 17 (good), 23 in the cycle II (good) and 27 in the cycle III (very good). Then, the classical completeness was 73.81 % in the cycle I and 83.33 % in the cycle II, and 100 % in the cycle III. Therefore, it can be concluded that Example Non-example model by using audio-visual media can improve the quality of IPA learning.